Creditor protection, judicial enforcement and credit access. Issue 3 (11th February 2018) - Moro, Andrea; Maresch, Daniela; Ferrando, Annalisa
ABSTRACT: We investigate the impact of the legal system on whether firms obtain the credit they apply for or not. Data comprise unique information provided directly by 48, 590 firms from 11 European countries. We look at the strength of creditor protection, the strength of property rights, the time taken to resolve a dispute, the dispute resolution process's costs and the number of procedures the plaintiff faces using data provided by the World Bank and the Heritage Foundation. The results suggest that the more efficient the judicial enforcement system is, and the higher the creditor protection is, the lower the probability that the firms are partially or totally denied credit. Our results are robust to selection bias (Heckman selection) as well as different controls and different estimation techniques. We find that these variables have considerable economic impact: the probability of obtaining credit is up to 40% higher in countries with more robust legal systems.